A new species of Galumnella (Acari, Oribatida, Galumnellidae) from Vietnam - Kolesnikov, Vasiliy B.; Leonov, Vladislav D. (Zootaxa, 2024)
The article describes a new species, Galumnella subiasi sp. nov., from Vietnam, which is distinguished from others by the following combination of characteristics: the notogaster, pteromorphs, prodorsum, and ventral shield have a network pattern; there is an interlamellar ridge on the prodorsum; lamellar and sublamellar lines are parallel; rostral and lamellar setae of medium length; bothridial setae slightly expanded in the middle, unilaterally heavily spinose; notogaster with 10 pairs of short setae; the adanal setae ad3 are located anterior to the anal aperture; postanal porose area absent; all leg tarsi with three claws. An identification key is provided for all Asian species of Galumnella, and it is demonstrated that Galumnella angustifrons and Galumnella nipponica are distinct species.